Analyzing junior high school students' mathematical reasoning in problem-solving: A focus on the Treffinger-oriented learning approach - Hidayah, Defi Fatikhatul; Hw, Slamet (Indonesian Journal of Science and Mathematics Education, 2024)
Mathematical reasoning is a fundamental ability that helps students solve various problems. This study aims to analyze students' mathematical reasoning in solving word problems using the Treffinger approach. This qualitative research with a phenomenological design involves researchers as the main instrument and uses mathematical reasoning tests and interview guides. The results showed that students tend to reread problems and annotate them before presenting mathematical ideas, indicating the positive influence of the Treffinger approach. Students use scratch sheets to justify answers and check the validity of their problem-solving steps, although some students still make mistakes in previous stages. The results show that the Treffinger approach encourages students' reasoning abilities in solving problems, from presenting the problem to checking the validity of the answer. However, students' understanding of mathematical concepts is also essential in problem-solving. This research implies an alternative solution for teachers to improve students' mathematical reasoning abilities through classroom learning.